A square-pyramidal coordinated copper(ii) hydrazine dimeric complex showing reversible phase transition, dielectric anomaly and thermochromism. (8th December 2020) - Ke, Shanxue; Li, Mingli; Rao, Wenjun; Wei, Zhenhong; Cai, Hu
Abstract : A square-pyramidal coordinated copper(ii ) hydrazine dimeric complex was prepared by reaction of CuCl2 with trimethyl hydrazine showing reversible phase transition, dielectric anomaly and thermochromism. Abstract : Recently, the development of multifunctional thermochromic materials that exhibit switching characteristics in phase transition and dielectric properties has attracted widespread attention due to their potential application in signal processing and smart devices. But most traditional thermochromic materials tend to be rather than reversible phase change materials. Here, a square-pyramidal coordinated copper complex [Me3 NNH2 CuCl3 ]2 (1 ) (Me3 NNH2 = trimethyl hydrazine) showing switchable properties in phase transition, dielectricity and thermochromic properties has been prepared by reaction of Me3 NNH2 I with CuCl2 in concentrated HCl aqueous solution. Compound 1 has a reversible phase transition temperature of 45 °C. When the temperature exceeds the phase transition temperature, the green color of 1 gradually changed into dark red. Compared with traditional thermochromic materials, the reversible phase transition and dielectric properties within the thermochromic materials will bring additional spectral encryption possibilities for future information processing.